Integrating GWAS, linkage mapping and gene expression analyses reveal the genetic control of first branch height in Brassica napus L - Dong, Zhixue; Tang, Minqiang; Cui, Xiaobo; Zhao, Chuanji; Tong, Chaobo; Liu, Yueying; Xiang, Yang; Li, Zaiyun; Huang, Junyan; Cheng, Xiaohui; Liu, Shengyi (Frontiers in Plant Science, 2022)
Rapeseed is a crucial oil crop cultivated across the world. The first branch height (FBH), an essential component of plant architecture in Brassica napus, has important effect on yielding and mechanized harvesting, but the genetic mechanism remains unclear. In this study, based on the 60K SNP array and a recombinant inbred lines (RILs) population of M083 and 888-5, a total of 19 QTL was detected in five environments, which distributed on A02, A09, A10, C06, and C07 linkage group, and explained phenotype variation ranging from 4.87 % to 29.87 %. Meanwhile, 26 significant SNPs were discovered on Chr.A02 by genome-wide association study (GWAS) in a diversity panel of 324 re-sequencing accessions. Then the major QTL of FBH trait was co-located on Chr.A02 by integrating linkage mapping and GWAS. 11 candidate genes were screened by allelic variation analysis, inter-subgenomic synteny analysis and different expression genes of parental shoot apical meristem tissues. Among these genes, BnaA02g13010D, which encodes a TCP transcription factor, was confirmed as the target gene according to gene function annotation, haplotype analysis, and full-length gene sequencing revealed that TATA insertion/deletion in the promoter region was closely linked to significant difference of phenotype. Over-expression of BnaA02.TCP1M083 lines presented decreased branch height and increased branch number in Arabidopsis. These results provide a genetic basis for FBH and ideal plant architecture in B. napus.